The Global South and Comparative Constitutional Law - Dann, Philipp (Oxford Comparative Constitutionalism Ser, 2020)
Although the Global South represents 'most of the world' in terms of constitutions and population, it is underrepresented in comparative constitutional discourse. This book fills the gap in this scholarship by tackling the most important aspects of comparative law from the Southern perspective